The Allanooka-Casuarinas Groundwater Investigation, Northern Perth Basin, Western Australia - Schafer, D.; Harris, Brett; Meredith, K.; Kern, A. (Australian Water Association, 2013)
This paper presents results from a recent comprehensive groundwater investigation of the Allanooka and Casuarinas groundwater subareas in the Northern Perth Basin. Several activities were completed as part of the investigation including; airborne electromagnetic surveying, high resolution seismic reflection, investigation drilling, construction of monitoring bores, water level monitoring, sampling for groundwater chemistry and isotopes analysis. The methods deployed at Allanooka were found to be complementary and have facilitated a greatly improved conceptual understanding in a complex hydrogeological environment. 3-D maps showing salinity distribution have been developed and faults that have major influence on groundwater flow are identified. Assessment of the results demonstrates that an actively recharged, fresh groundwater-flow system, with up to 200 m of fresh groundwater, is underlain by a deep, brackish to saline, slow-moving groundwater Basin-scale solute distribution is shown to be impacted by recharge rates, groundwater flow rates and lithology changes across major faults. Results from this investigation support water resource management and planning initiatives in an area where freshwater resources are in demand and requires careful management.